Landsat 8 Imagery Utilization to Spatial Analysis of Rehabilitation and Reconstruction of Palu Disaster in 2018 - Westi Utami; Yuli Ardianto Wibowo; Fajar Buyung Permadi; Wasyilatul Jannah (BHUMI: Jurnal Agraria dan Pertanahan, 2019)
Rehabilitation and reconstruction as a post-disaster stage becomes an important part in the disaster management cycle. Post-disaster as a moment that can be used to rebuild a better life order must be optimized in its implementation. This study was conducted using a spatial approach through the use of multitemporalremote sensing satellite imagery in Palu region. The data used in this study are Landsat 8 images in March 2018, Landsat 8 in November 2018 and Landsat 8 in March 2019. The research method is carried out through spatial analysis by supervised classification which is the maximum likelihood algorithm for classifying land use. The analysis was conducted by supervising classification to classify the existing conditions of land use. The research indicates that the locations of residential development are determined by the Government which are located inthe urban village of Tondo, sub-district of Mantkulore and urban village of Duyu, sub-district of West Palu, Palu City district; and they have considered the aspect of disaster vulnerability and land availability. The analysis of Landsat imagery shows that in this area, the rehabilitation and reconstruction process is ongoing. By theanalysis, it is discovered that there are changes in land-use before and after the disaster. In November 2018, there was a decrease of 56.4 hectares of built land in the village of Tondo and 17.76 hectares in village of Duyu. While, the results of the Landsat 8 image study in March 2019 shows that there are increases in these two regions.